Perceived musical and non-musical benefits of participating in choral activities among music and non-music majors / Cylvesora Paunus - Paunus, Cylvesora (Faculty of Music, 2017)
The purpose of this study was to examine the perceived musical benefits of participating in choral activities among music and non-music majors and to explore the perceived non-musical benefits of participating in choral activities among music and non-music majors. The sample of this study were music and non-music majors with total of 100 respondents of whom all are undergraduate students from three different university around Selangor which are Universiti Teknologi MARA (UiTM), Universiti Putra Malaysia (UPM) and Universiti Malaya (UM). Data was collected through Google form and e-mail. There are 4 variables for the research which are musical benefits, social benefits, physical benefits and emotional benefits. Based on the findings, most of the respondent believed that their participation in choral activities helped them in gaining musical and non-musical benefits. Although half of the respondent are not majoring in music, but it shows that they have the same vision as the music majors. From the results, we can have summarized that students can perceived musical and non-musical benefits for their participation in choral activities.